An automated assay for the assessment of cardiac arrest in fish embryo. (1st February 2017) - Puybareau, Elodie; Genest, Diane; Barbeau, Emilie; Léonard, Marc; Talbot, Hugues
Abstract: Studies on fish embryo models are widely developed in research. They are used in several research fields including drug discovery or environmental toxicology. In this article, we propose an entirely automated assay to detect cardiac arrest in Medaka ( Oryzias latipes ) based on image analysis. We propose a multi-scale pipeline based on mathematical morphology. Starting from video sequences of entire wells in 24-well plates, we focus on the embryo, detect its heart, and ascertain whether or not the heart is beating based on intensity variation analysis. Our image analysis pipeline only uses commonly available operators. It has a low computational cost, allowing analysis at the same rate as acquisition. From an initial dataset of 3192 videos, 660 were discarded as unusable (20.7%), 655 of them correctly so (99.25%) and only 5 incorrectly so (0.75%). The 2532 remaining videos were used for our test. On these, 45 errors were made, leading to a success rate of 98.23%. Abstract : Graphical abstract: fx1 Abstract : Highlights: An automated method to detect the presence of a heartbeat in fish embryos, using video sequence analysis is proposed. Heartbeat detection is based on measuring cyclic intensity variations in the thorax region of the embryo. Image stabilization and spurious motion detection is performed to eliminate motion artifacts. The procedure works on both eggs and hatched embryo.